Highly Shielded Peroxo‐Cerium(IV)‐Containing Polyoxometalate: Synthesis, Structure, and Oxidative Studies - Anusree Sundar; Danica Bajuk‐Bogdanović; Gordana Ćirić‐Marjanović; Talha Nisar; Veit Wagner; Arnulf Materny; Geoffrey B. Jameson; Bassem S. Bassil; Ulrich Kortz (ChemistryEurope, 2025)
The peroxo‐bridged di‐cerium(IV)‐di‐lithium‐containing polyoxometalate [(CeIV2O2)Li2(P2W16O59)2]16− (Ce2Li2P4W32) is synthesized in a one‐pot aqueous synthetic procedure and isolated as a hydrated mixed alkali salt, K13.6Na1.4Li[(CeIV2O2)Li2(P2W16O59)2]·32H2O (KNaLi‐Ce2Li2P4W32). The novel polyanion Ce2Li2P4W32 comprises a side‐on peroxo‐group bridging two cerium(IV) and two lithium ions, which are encapsulated between two dilacunary, face‐on P2W16 Wells–Dawson units, with a vacant site in each of the two belts. The polyanion Ce2Li2P4W32 is characterized in the solid state by single‐crystal X‐ray diffraction, Fourier transform infrared spectroscopy, thermogravimetric analysis, X‐ray photoelectron spectroscopy, and Raman spectroscopy and in solution by 31P NMR and Raman spectroscopy, respectively. Ce2Li2P4W32 and the peroxo‐group are shown to be highly stable in a large pH range and up to almost boiling temperatures, but at the same time the polyanion is reactive toward oxidation of triphenylphosphine, involving the peroxo group and the cerium(IV) centers.